MODERN APPROACHES TO THE ACTIVITY OF A SPECIALIZED SUBJECT TEACHER AT THE FACULTY OF HIGHER NURSING EDUCATION (International journal of medical sciences, 2026)
This article analyzes the role of a specialized subject teacher at the Faculty of Higher Nursing Education, their professional and pedagogical competencies, as well as the effectiveness of applying modern educational technologies and interactive methods. The research findings demonstrate the contribution of these approaches to the training of qualified personnel in the field of nursing.